The Impact of ChatGPT Dependence and Inert Thinking on Students' Academic Task Completion - Wahyuni Edsa Safira; Udin Sidik Sidin; Dwi Rezky Anandari Sulaiman (Information Technology Education Journal, 2025)
The increasing use of Artificial Intelligence (AI), particularly ChatGPT, among students has raised concerns about the emergence of inert thinking (passive thinking) and overreliance on technology in completing academic tasks. Guided by Inert Knowledge Theory and Dual Process Theory, this study analyzes the relationship between inert thinking and ChatGPT dependence on academic task completion among Informatics and Computer Engineering students at Makassar State University. Using a quantitative survey method, data were collected from 225 respondents through a snowball sampling technique and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The findings reveal that passive thinking significantly reduces students’ ability to complete academic tasks, while dependence on ChatGPT strongly increases inert thinking. However, ChatGPT dependence itself does not directly enhance task completion. These results indicate that excessive reliance on AI tools tends to weaken reflective and critical thinking processes, limiting students’ self-regulated learning. This study highlights the importance of responsible AI use in higher education to maintain cognitive engagement and academic integrity. Educators and policymakers should develop strategies and digital literacy programs that encourage reflective learning and critical evaluation, ensuring AI serves as a supportive tool, not a substitute for human thinking